THE MEASUREMENT OF PROPER HANDWASH KNOWLEDGE ON ELEMENTARY AND HIGHSCHOOL STUDENTS - Yesita Sandi Langitan; Maria Paulina Wauran; Sara Agustina; Sondang Lusiana Sitinjak; Lyna Hutapea (Jurnal Cakrawala Ilmiah, 2023)
Washing hands has proven to be one of the most crucial ways of preventing diseases from entering our body, as it is an effort to kill the pathogenic microorganisms that come in contact with the body surface. However, due to its simplicity in doing, the behavior of proper hand washing has been ignored by many, leading to increased susceptibility of diseases, particularly of the gastrointestinal system, including diarrhea. This study is done to measure the knowledge of elementary and high school students of SD and SMP Advent Setiabudi on proper hand washing, including 13 participants, extracted from 195 students as population. It is done systematically utilizing the qualitative method. It is found that the knowledge of handwashing and its procedure have been introduced to most of the students yet some participants have been found to not apply the behavior of washing hands with soap which have been proven to kill more microorganisms than just flowing water without soap. It is concluded that the application of proper handwashing must be promoted more among the general population as knowing is not enough. The researchers then recommend for the healthcare and school personnel to hold community health educations as a contribution in raising the awareness which can raise the implementation of proper hand washing with soap in order to prevent diseases from happening.